Service of scholars of Uzbekistan during the Second Renaissance (Eurasian Journal of Humanities and Social Sciences, 2024)
This article examines the significant contribution of Uzbek scientists during the second renaissance, the revival of intellectual, cultural and scientific achievements. As a result of the research, the information about science was enslaved by Uzbek scientists in style, studied in depth, and their results were covered. The conclusion provides insight into the long-term impact of their services and offers suggestions for further development of scientific excellence.